If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -29 = x + 7 Reorder the terms: -29 + 5x = x + 7 Reorder the terms: -29 + 5x = 7 + x Solving -29 + 5x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -29 + 5x + -1x = 7 + x + -1x Combine like terms: 5x + -1x = 4x -29 + 4x = 7 + x + -1x Combine like terms: x + -1x = 0 -29 + 4x = 7 + 0 -29 + 4x = 7 Add '29' to each side of the equation. -29 + 29 + 4x = 7 + 29 Combine like terms: -29 + 29 = 0 0 + 4x = 7 + 29 4x = 7 + 29 Combine like terms: 7 + 29 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 2a^3-3a^2-4a+6=0 | | 8b+4=6b-10 | | 5+3(q-4)=2(2q+1) | | 295x+350x+39=33x | | 5p-10-2p+21=-1 | | 2(-x)+x+(-x+2)=x | | -4-3x=-x-8 | | x-17=4x+4 | | 5x-2=6x+-8 | | 8x=8(x-1)+1 | | 4x^2+28x+50=0 | | 9d+35=4d | | x-3=5x+1 | | -1+4x-3x=7 | | (2k+1)=5(k-2) | | (2x-3y)(x-3y)= | | 250=14x+22x | | 4x-10+2x=62 | | 3(s+22)=4(s+2) | | 3(1-r)+5r=4(r+1)+5 | | 5+x+-3x=3x-2x-1 | | 3.4t+0.008=11 | | -x-30=3x+6 | | 45=3V | | -4r+5=2(2.5-2r) | | M^2+6m-16= | | 14-3(5t+-12)=1-(20t+1) | | 6z-4=9z+14 | | 8x+16=22+8x | | -33=r+(-26) | | (-5)+(9)= | | 14xy-7x^2+5x=0 |